How Organizational Citizenship Behavior Stimulant: Transformational Leadership Identification Model Approaches - Mochamad Soelton; Agus Arijanto; Yanto Ramli; Suprapto; Irmayunita; Subur Karyatun; Anees Janee Ali (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Workers with Organizational Citizenship Behavior (OCB) are more likely to put in more effort and go above and beyond what is required of them. Workers who accept the company's aims and values and step up their efforts to work hard for the company's advantage, and are proud of their company, the employee's willingness to take on a role that exceeds his main role in an organization, is referred to as extra-role behavior. Purpose: This research aims to analyze the influence of Transformational Leadership and Job Satisfaction on Organizational Citizenship Behavior (OCB) with Organizational Commitment as a mediating variable in National Gas Company. Design/methodology/approach: The data collection method uses a survey method, with the research instrument in the form of a questionnaire. The analysis used is statistical analysis in the form of SEM-PLS.Findings/Result: The results of this research prove that transformational leadership has a positive and significant effect on OCB, the impact of job satisfaction on overall corporate branding (OCB) is both positive and not significant. However, the combination of job satisfaction and transformational leadership has a positive and significant effect on organizational commitment, which in turn has a positive and significant effect on OCB. While organizational commitment cannot mediate the influence of job satisfaction on OCB, it can partially mediate the influence of transformational leadership on OCB.Conclusion: Leaders who have the ability to lead with a good transformational style will create an atmosphere of OCB among most of their employees, including employee work engagement will increase if the organization has a transformational leadership style. Including high and low job satisfaction does not affect the high or low level of employee OCB. Satisfied workers often exhibit high OCB behavior, which improves overall business success in the long run. This condition can trigger an increase in individual performance which will ultimately improve overall organizational performance.Originality/value (State of the art): The study's intriguing conclusion is that there is no significant relationship between work satisfaction and OCB. This condition is possible because employees are able to behave in ways that exceed what is standardized by the employees themselves (beyond expectations), so that high job satisfaction does not necessarily encourage someone to carry out OCB as expected company. Keywords: transformational leadership, job satisfaction, organizational citizenship behavior (OCB), organizational commitment, SEM-PLS